Values in the sphere of marriage and family relations in the context of modern transformations of society - P. A. Balyavina; M. R. Danilova (Цифровая социология)
Family is the basic unit of society which plays a key role in the primary socialisation of an individual. It is in the family that a person learns norms and values that later determine his/her behaviour and interaction with other people. However, in the modern world, marriage and family values are undergoing significant changes which leads to the transformation of social interaction. This article analyses the factors influencing the formation of value orientations of modern youth in the sphere of family and marriage. The research studies trends in the development of family and marriage relations in the current Russian society, examines value orientations of young people and identifies factors that have the greatest impact on their establishment. The relevance of the article is conditioned by the need to understand the mechanisms of this establishment in today’s society. The results of the paper can be used and are helpful to develop recommendations on the formation of family values and strengthening the family institution, to develop educational programmes and courses in sociology, psychology, pedagogy, and other disciplines related to the study of family and family values. The work is based on the analysis of scientific publications, statistical data, and other sources of information.